Determining A Technology for Development of the Mechanism of Anti-Crisis Management of the Agro-Industrial Complex - Kitovich Tkhakushinov, Edward; Aslanovna Hachemizova, Emma (International Journal of Engineering and Technology, 2018)
This article is devoted to effective management of the agro-industrial complex (AIC) in the context of crises, the impact of which on the economic efficiency of AIC subjects was made on various aspects of economic activity. A variety of factors, from a sharp change in the level of inflation to a change in energy prices and demand for agricultural products, have determined the need for a timely response of AIC subjects, as well as the adaptation of the system and management methods to the sharply changing environmental conditions.The structural and logical scheme is proposed, which will allow structuring the general process of crisis management and determining its main functions and monitoring tasks.The structure and the system for calculating the alternatives for the development of crisis situations are complex and cover all elements of the regional AIC. Moreover, they are based on a combination of technical and software tools, implementing automation ideas and methods based on modern mathematical tools.Â Â